2018
DOI: 10.1089/neu.2017.5174
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Field of View Diffusion Tensor Imaging and Fiber Tractography of the Pediatric Cervical and Thoracic Spinal Cord Injury

Abstract: The aim of this study is to assess the utility and effectiveness of diffusion tensor imaging (DTI) and diffusion tensor tractography (DTT) of the entire pediatric cervical and thoracic spinal cord toward discrimination of typically developing (TD) controls and subjects with spinal cord injury (SCI). A total of 43 pediatric subjects, including 23 TD subjects ranging in age from 6 to 16 years old and 20 subjects with SCI ranging in age from 7 to 16 years, were recruited and scanned using a 3.0 Tesla magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Thus, we proposed the hypothesis that the combinative application of conventional MRI, DTI, and DTT be effective in evaluation of SCI and PTS. This hypothesis concurs with the latest published clinical reports [ 19 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we proposed the hypothesis that the combinative application of conventional MRI, DTI, and DTT be effective in evaluation of SCI and PTS. This hypothesis concurs with the latest published clinical reports [ 19 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…DTT can visualize the injury epicenter and the interrupted spinal cord tracts. DTI is a useful quantitative evaluation for nerve degeneration and axonal loss, as changes in axonal structure can affect the diffusion of water molecules [ 15 , 16 ]. A series of studies have concluded that FA values decrease and ACD values increase at lesion sites after SCI [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fiber tracts of the brain were generated using a deterministic streamline approach. This method has proven to be an effective algorithm capable of estimating the trajectories of white matter tracts in the brain and the cord 2628 . However, deterministic fiber tracking has limitations, particularly in voxels where fibers are crossing, bending or kissing.…”
Section: Discussionmentioning
confidence: 99%
“…DWI stitching is difficult to perform and is sensitive to artifacts produced by respiratory and cardiac movements at the thoracic level of the spinal cord 9,57 . Nonetheless, several teams 14,58,59 have aimed to perform DWI and tractography of the entire spinal cord. Regardless of the MRI manufacturer, the field of view is not large enough to cover the entire spinal cord.…”
Section: Discussionmentioning
confidence: 99%